Charge Transfer: Interfacial Design and Assembly for Flexible Energy Electrodes with Highly Efficient Energy Harvesting, Conversion, and Storage (Adv. Energy Mater. 27/2021). Issue 27 (22nd July 2021) - Ko, Yongmin; Lee, Seokmin; Kwon, Cheong Hoon; Lee, Seung Woo; Cho, Jinhan
Abstract : Charge transfer kinetics within nanoparticle‐based energy electrodes play a decisive role in achieving higher output performance. In article number 2002969, Seung Woo Lee, Jinhan Cho and co‐workers review the progress in various electrodes that have been prepared for improved charge transfer. This image depicts the moment when bulky organic ligands bound to nanoparticles are replaced via a small molecular ligand‐containing solution.